Montenegrin rural settlement attributes, problems, and possibilities for development according to their regional affiliation - Mašanović, Nevena (Array, 2021)
The rural areas cover a significant part of the Montenegrin territory and play an essential role in its development potential. These areas have been exposed to various (more spontaneous and less planned) transformations throughout history, which has been reflected in their particular characteristics. The three settlements, one from each region, were treated by analyzing identity attributes and complex issues of development and degradation of rural areas. This research aims to determine the reasons for the extinction of rural settlements and propose measures for preserving the existing and restoration of the missing values of their natural and cultural heritage. The planning procedures for recognizing and determining the criteria for the detection (today visible ones) and assessing the lost values of rural settlements are proposed at the end of this paper. Future planning and design processes could acquire the gained knowledge about these values and be employed through future development, through creating new planning and economic models for the rural settlements' revival, protection, and improvement.